Conceptualising a systems thinking perspective in sport studies. (21st March 2021) - Vermeulen, Euodia; Grobbelaar, Sara S.; Botha, Adele
Abstract: To date, applications of Systems Thinking (ST) in sport sciences are lacking with little existing practical work that adopted the approach. The aim of the article is to present an instantiation of ST in running towards demonstrating its utility. Two qualitative, principle tools in ST is demonstrated for a systemic problem in sport, namely recurring overuse injuries related to running. First, the growth-and-underinvestment system archetype is illustrated as a mechanism to differentiate short and long term solutions, incorporating the recent Nike Vaporfly running shoes and gait retraining. Secondly, a populated ice-berg model is provided of the runner and their environment: the runner-environment system is broken down into constituent units and then synthesised as the synergy between units; specifically considering the runner's biomechanical properties, wearables and social media platforms. This article forms part of a more extensive project to contribute to a practical departure for ST in sport science; future work includes the quantified dynamic model of injury development from emergent interactions.